The Relationship Between Social Support and Prisoners’ Compliance in Rehabilitation Activities at Class II Penitentiary Padang - Puteri Aneira Muthie Syade; Rinaldi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
The effectiveness of rehabilitation programs in correctional facilities depends not only on institutional regulations but also on the psychosocial support received by inmates. This study employed a quantitative correlational design to examine the relationship between social support and prisoners’ compliance in rehabilitation activities at the Class II Padang Penitentiary. The population consisted of 60 inmates participating in NAPZA rehabilitation, and total sampling was used to include all individuals as respondents. Data were collected using a structured questionnaire and analyzed to determine the association between perceived social support and compliance levels. The results indicate a statistically significant and strong positive relationship between social support and prisoners’ compliance. Inmates who receive higher levels of social support tend to demonstrate greater adherence to rehabilitation programs, reflecting the motivational and behavioral benefits of a supportive social environment. These findings emphasize the crucial role of social support in fostering engagement, commitment, and positive behavioral outcomes in correctional rehabilitation settings. This study provides empirical evidence highlighting social support as a key factor in enhancing the effectiveness of rehabilitation programs. The findings have practical implications for correctional policy and intervention design, suggesting that strengthening social support mechanisms within and beyond the penitentiary can improve inmates’ participation and compliance. Future research is encouraged to explore additional influencing factors and adopt longitudinal approaches to better understand changes in compliance behavior over time.